The Mediating Role of Talent Management in Succession Planning and Private Organization Sustainability: A Conceptual Article - Samuel, Idemi; Isa, Mohd Yaziz Mohd (Journal of Current Social and Political Issues, 2024)
In the contemporary landscape of business, talent management has emerged as a strategic imperative for organisations aiming to enhance their performance and ensure long-term sustainability. The recognition of talent management's significance lies in its ability to attract, retain, and nurture key talents within an organisation. This process is particularly crucial for private enterprises, where human capital plays a pivotal role in driving innovation, productivity, and competitive advantage. Talent management operates within the broader framework of succession planning, which itself is a critical component of effective human resource planning. Succession planning involves identifying and developing internal talent to fill key leadership positions as they become vacant. This proactive approach not only mitigates the risks associated with leadership transitions but also ensures continuity and stability within the organization. This study delves into the intricate relationship between talent management and succession planning, specifically focusing on their impact on organizational sustainability. By conducting a comprehensive review of existing literature, the study aims to uncover insights into how talent management practices contribute to shaping effective succession planning strategies. Key areas of investigation include planning practices, training and development initiatives, performance appraisal systems, talent retention strategies, and overall talent management policies. Through the proposed conceptual model, the study seeks to elucidate the dynamics that connect succession planning and organizational sustainability within the context of talent management. By integrating these elements, organizations can better align their talent strategies with long-term sustainability goals, thereby enhancing their resilience and competitive positioning in the Nigerian business landscape.